Reductionism at the vertebrate kinetochore - Stankovic, A. (2015)
The kinetochore forms the site of attachment for mitotic spindle microtubules driving chromosome segregation. The interdependent protein interactions in this large structure have made it difficult to dissect the function of its components. In this issue, Hori et al. (2013. J. Cell Biol. http://dx.doi.org/10.1083/jcb.201210106) present a novel and powerful methodology to address the sufficiency of individual proteins for the creation of a functional de novo centromere.